Job satisfaction, work commitment, and intention to leave among cardiac technologists in Saudi Arabia - Lamia Al Saikhan (Preventive Medicine Reports)
Objectives: We examined the factors influencing job satisfaction and work commitment among cardiac technologists across different healthcare settings, and the influence of these factors on the likelihood of leaving their current job. Methods: In this cross-sectional study, an online self-administered survey using a previously validated questionnaire was distributed from August to November 2022 to all graduates of the cardiac technology program at the Imam Abdulrahman bin Faisal University in the Eastern Province of Saudi Arabia between 2013 and 2022. Results: Of 204 graduates, 141 completed the survey(69.1 % response rate). Of these, 105(74.5 %) were employed during the survey and included in the final analysis. All respondents were women, and the majority(76.9 %) were aged 25–30 years, had a bachelor's degree(95.2 %), and were per-forming noninvasive procedures(echocardiography; 68.3 %). Most respondents worked eight to nine hours daily, and 56.6 % worked at government hospitals. Most respondents reported some level of job satisfaction with their current job(12.4 %, 35.2 %, and 25.7 % were extremely satisfied, satisfied, and slightly satisfied, respectively). However, 54 % of the respondents still intended to leave their current jobs. Their likelihood of leaving their current job was associated with place of practice(p = 0.01) and monthly income(p = 0.00). Place of practice, overnight call system, day/night shift system, and monthly income were associated with job satisfaction and work commitment(p < 0.05). Conclusions: The surveyed cardiac technologists were mostly satisfied with and relatively committed to their current jobs. However, they intended to leave. Future research exploring the reasons behind cardiac technologists' intentions to leave their cardiac technology practice jobs is needed.